2010
DOI: 10.1111/j.1365-2516.2010.02364.x
|View full text |Cite
|
Sign up to set email alerts
|

Does haemophilia influence cancer‐related mortality in HIV‐negative patients?

Abstract: Clinical investigations and animal studies suggest haemophilia specific effects on cancer-related mortality aside from virus induced malignancies. Analysis of results in the literature proposes that coagulation factor deficiency might inhibit cancer metastasis through decreased activation of thrombin. On the other hand, substitution of coagulation factor might increase cancer rates. A review of epidemiological studies was conducted to survey the clinical data on cancer rates. Clinical investigations concerning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…A survey on 717 Dutch patients with hemophilia has revealed that individuals with hemophilia have a protection against ischemic heart disease, whereas it has been reported there are more cancer-related mortalities. 20 There were 6 episodes of death due to various cancers, whereas in the current survey, there was only death due to heart problems. This may be relevant somehow to the fluctuation in the pattern of deaths among developed and developing countries.…”
Section: Discussionmentioning
confidence: 78%
“…A survey on 717 Dutch patients with hemophilia has revealed that individuals with hemophilia have a protection against ischemic heart disease, whereas it has been reported there are more cancer-related mortalities. 20 There were 6 episodes of death due to various cancers, whereas in the current survey, there was only death due to heart problems. This may be relevant somehow to the fluctuation in the pattern of deaths among developed and developing countries.…”
Section: Discussionmentioning
confidence: 78%
“…In contrast with these findings, other studies have found a similar or even higher rate of non‐HIV/HCV‐related cancers in hemophiliacs than in non‐hemophiliacs [18,19]. In a recent review on epidemiological studies regarding cancer in hemophilia, Miesbach and Seifried [6] found that non‐HIV/HCV‐related cancers accounted for 8–16% of all deaths in hemophiliacs with a SMR lower than one in all studies, indicating a lower cancer mortality in the virally uninfected hemophilia population than in the matched general male population. The low SMR due to non‐HCC/HIV‐related cancers found in the present study (0.3) is in keeping with the majority of literature data and confirms the results from our previous study [2].…”
Section: Discussionmentioning
confidence: 97%
“…14 A previous study by Rabkin et al in 1992 showed that with the exception of Kaposi's sarcoma and Non-Hodgkin's lymphoma, cancer incidence was not increased in hemophilic HIV-positive patients compared to the general population of the United States. 15 Similar results were also seen in an Italian study by Tagliaferri et al 16 Our study showed that hemophilic HIV-positive patients were also at increased risk of cancers of the oral cavity, oropharynx and hypopharynx, and larynx when compared to the general population of Taiwan.…”
Section: To the Editorsmentioning
confidence: 95%